Rate of detection of serrated lesions at colonoscopy in an average-risk population: a meta-analysis of 129,001 individuals - Huang, Junjie; Chan, Paul S.F.; Pang, Tiffany W.Y.; Choi, Peter; Chen, Xiao; Lok, Veeleah; Zheng, Zhi-Jie; Wong, Martin C.S. (Endoscopy International Open, 2021)
Background and study aims Serrated lesions are precursors of approximately one-third of colorectal cancers (CRCs). Information on their detection rate was lacking as an important reference for CRC screening. This study was a systematic review and meta-analysis to determine the overall detection rate for serrated lesions and their subtypes in average-risk populations undergoing CRC screening with colonoscopy.Patient and methods MEDLINE and Embase were searched to identify population-based studies that reported the detection rate for serrated lesions. Studies on average-risk populations using colonoscopy as a screening tool were included. Metaprop was applied to model within-study variability by binomial distribution, and Freeman-Tukey Double Arcsine Transformation was adopted to stabilise the variances. The detection rate was presented in proportions using random-effects models.Results In total, 17 studies involving 129,001 average-risk individuals were included. The overall detection rates for serrated lesions (19.0 %, 95 % CI = 15.3 %–23.0 %), sessile serrated polyps (2.5 %, 95 % CI = 1.5 %–3.8 %), and traditional serrated adenomas (0.3 %, 95 % CI = 0.1 %–0.8 %) were estimated. Subgroup analysis indicated a higher detection rate for serrated lesions among males (22.0 %) than females (14.0 %), and Caucasians (25.9 %) than Asians (14.6 %). The detection rate for sessile serrated polyps was also higher among Caucasians (2.9 %) than Asians (0.7 %). Conclusions This study determined the overall detection rate for serrated lesions and their different subtypes. The pooled detection rate estimates can be used as a reference for establishing CRC screening programs. Future studies may evaluate the independent factors associated with the presence of serrated lesions during colonoscopy to enhance their rate of detection.